Selected problems related to the implementation of a new electronic delivery system in administrative proceedings (Discourse of Law and Administration, 2024)
The subject of the study are selected problems related to the implementation of a new type of electronic deliveries in administrative proceedings. The Act of 18 November 2020 on Electronic Deliveries introduced a dualistic structure of the electronic delivery system to be used by public entities. Public services, hitherto unknown to Polish law, were standardized: the public service of registered electronic delivery and the public hybrid service, and the default digitization of deliveries of public entities was introduced. Against this background, the article discusses doubts regarding the legal regulation of the material scope of the use of new e-delivery, in connection with the exclusions specified in art. 3 and 6 of the Act and the provisions of the Code of Administrative Procedure. The issue of the temporal scope of the e-delivery reform was also presented in connection with the regulations of the transition period and the announcement by the Minister of Digitization , specifying the date of application of the new delivery services on 1 January 2025.
Keywords: e-delivery service; Act on Electronic Deliveries; public service of registered electronic; delivery; public hybrid delivery